2015
DOI: 10.3390/su71014287
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance Evaluation of Multistory Reinforced Concrete Moment Resisting Frame Structure with Shear Walls

Abstract: This paper is intended to evaluate the seismic performance of a twelve-story reinforced concrete moment-resisting frame structure with shear walls using 3D finite element models according to such seismic design regulations as Federal Emergency Management Agency (FEMA) guideline and seismic building codes including Los Angeles Tall Building Structural Design Council (LATBSDC) code. The structure is located in Seismic Zone 4, considered the highest-seismic-risk classification established by the U.S. Geological S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A fragility curve can be usually produced with the use of a mathematical function related to seismic capacity and demand of the structure, accounting for their uncertainties [31]. Mathematical function of fragility curves can be represented as follows [31]:…”
Section: Fragility Curvementioning
confidence: 99%
See 1 more Smart Citation
“…A fragility curve can be usually produced with the use of a mathematical function related to seismic capacity and demand of the structure, accounting for their uncertainties [31]. Mathematical function of fragility curves can be represented as follows [31]:…”
Section: Fragility Curvementioning
confidence: 99%
“…is the logarithmic standard deviation for the capacity; and 0[ ] is the standard normal distribution function. The parameter was assumed to be 0.3 following the recommendations from HAZUS [31], while was computed as the logarithmic standard deviation of seismic responses gained for each floor of the studied structure from the nonlinearly dynamic analyses. As aforementioned, the maximum interstory drift ratios have been widely and efficiently used to generate fragility curves for multistory framing structures at predescribed FEMA different performance levels.…”
Section: Maximum Interstory Drift Ratio Maxmentioning
confidence: 99%
“…The study showed that near-source outcomes cause most of the seismic energy from the rupture to arrive in a single coherent longperiod pulse of motion and permanent ground displacements. Additionally, in some studies, the effects of NF and FF records on the RC structures were investigated [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with empirical fragility function on field data was also observed. Junwon Seo, Jong Wan Hu and Burte Davaajamts (2015) [23] evaluates the seismic performance of a twelve storey reinforced concrete moment resisting frame structure with shear walls using 3Dfinite element models. Two standard approaches response spectrum analysis and nonlinear time history analysis were used for seismic performance evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%